Cognitive Fatigue, Sleep and Cortical Activity in Multiple Sclerosis Disease. A Behavioral, Polysomnographic and Functional Near-Infrared Spectroscopy Investigation - Borragán, Guillermo; Gilson, Médhi; Atas, Anne; Slama, Hichem; Lysandropoulos, Andreas; De Schepper, Melanie; Peigneux, Philippe (Frontiers in Human Neuroscience, 2018)
Patients with multiple sclerosis (MS) disease frequently experience fatigue as their most debilitating symptom. Fatigue in MS partially refers to a cognitive component, cognitive fatigue (CF), characterized by a faster and stronger than usual development of the subjective feeling of exhaustion that follows sustained cognitive demands. The feeling of CF might result from supplementary task-related brain activity following MS-related demyelination and neurodegeneration. Besides, CF in MS disease might also stem from disrupted sleep. The present study investigates the association between the triggering of CF, task-related brain activity and sleep features. In a counterbalance mixed design, 10 patients with MS and 11 healthy controls were exposed twice to a cognitively demanding task aimed at inducing either high or low levels of CF. Considering known inter-individual differences and potential cognitive deficits in MS, the cognitive load of the task was individually adapted to each participant's own limits. During the experimental sessions, cortical brain activity was measured using near-infrared spectroscopy (NIRS) during the CF-induction task, and in a resting state before and after. Ambulatory polysomnography recordings were obtained on the preceding nights. At neuropsychological testing, patients with MS exhibited reduced attentional and inhibitory control and slower information processing. However, when levels of cognitive load were individually adapted, they reported similar feelings of CF than controls, and exhibited similar behavioural performance and brain activity patterns. Linear mixed models indicate a negative association between oxygenation level changes in the dorsolateral prefrontal cortex (DLPFC) and the triggering of subjective CF in patients with MS only. Longer total sleep time was also associated with higher CF in MS patients.These results suggest that equalizing cognitive load between individuals with and without MS results in similar subjective CF levels. Although performance and cortical brain activity are comparable between groups, mixed model analyses suggest a possible association between CF, DLPFC activity and sleep duration.